2014
DOI: 10.1186/1756-9966-33-10
|View full text |Cite
|
Sign up to set email alerts
|

miR-302b is a potential molecular marker of esophageal squamous cell carcinoma and functions as a tumor suppressor by targeting ErbB4

Abstract: BackgroundErbB4 expression has been noted in various tumors, but its regulatory mechanism in esophageal squamous cell carcinoma (ESCC) remains unclear. The aim of this study was to investigate whether miR-302b regulates the expression of ErbB4 at the post-transcriptional level and to determine its expression, significance, and function in ESCC.MethodsWe used real-time reverse transcriptase-polymerase chain reaction to quantify the expression of miR-302b in 50 ESCC tissues and analyzed its relationship with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…(Fig. S4) The reason for these results is that miR-302b not only inhibited the expression of GCNT3, but also modulated the expression of its target genes, such as ERBB4, IRF2, CXCR4 [34], AKT2/NF-kB/MMP-2 pathway [35], CDK2 [36], ErbB4 et al [37], and AKT2 [38]. As we know, one single miRNA can regulate a broad range of cellular processes including cell growth, proliferation and apoptosis, by post-translational modulation of the target genes [13].…”
Section: Discussionmentioning
confidence: 91%
“…(Fig. S4) The reason for these results is that miR-302b not only inhibited the expression of GCNT3, but also modulated the expression of its target genes, such as ERBB4, IRF2, CXCR4 [34], AKT2/NF-kB/MMP-2 pathway [35], CDK2 [36], ErbB4 et al [37], and AKT2 [38]. As we know, one single miRNA can regulate a broad range of cellular processes including cell growth, proliferation and apoptosis, by post-translational modulation of the target genes [13].…”
Section: Discussionmentioning
confidence: 91%
“…By contrast, miR-197 was downregulated in esophageal cancer with a poor prognosis, and may play a tumor-suppressor role (13). Additionally, miR-302b inhibited cell proliferation by inducing apoptosis and suppressing the invasion in esophageal squamous cell carcinoma (14). miRNA profiling has shown that microRNA-374a (miR-374a) is overexpressed in many types of cancer, such as head and neck squamous cell carcinoma, follicular lymphoma, osteosarcoma and bladder urothelial carcinoma (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 94%
“…MiR-302b is a member of the miR-302 cluster, which consists of four homologous miRNAs that are transcribed as a noncoding RNA cluster and are specifically expressed in human and mouse embryonic stem cells [17]. MiR-302b acts as a tumor suppressor in esophageal squamous cell carcinoma and it is downregulated in hepatocellular carcinoma, where it inhibits cell proliferation by targeting EGFR [18,19]. Although genome-wide miRNA expression profiling studies showed that miR-302b is downregulated in ovarian carcinoma [14,20], the exact role of miR-302b in EOC remains unknown.…”
Section: Introductionmentioning
confidence: 99%